Getting Started with Tiva ARM Cortex M4 Microcontrollers A Lab Manual for Tiva LaunchPad Evaluation Kit - Gadre, Dhananjay V.; Gupta, Sarthak; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2018)
The book deals with laboratory experiments around ARM microcontroller. ARM microcontrollers, which are classified as 32-bit devices, are currently the most popular of all microcontrollers. They cover a wide range of applications that extend from traditional 8-bit devices to 32-bit devices. Of the various ARM sub-families, Cortex-M4 is a middle level microcontroller that lends itself well for data acquisition and control and digital signal manipulation applications. ARM microcontrollers are manufactured under license by dozens of manufacturers and Texas Instruments is one such prominent manufacturer.  Given the prominence of ARM microcontroller, it is important that it should be incorporated in academic curriculums. However, that doesn't seem to the case primarily because of the lack of teaching material - textbooks and comprehensive laboratory manuals. While there are a few textbooks, they are too out dated which has kept them from being considered as suitable teaching aids; there is atotal absence of any laboratory text dealing with contemporary offerings from the ARM family architecture.  The proposed lab manual deals with the architecture of the Tiva Cortex-M4 ARM microcontrollers from Texas Instruments. It describes various ways of programming these microcontrollers. The Tiva Launchpad - a low cost evaluation kit from Texas Instruments is used in this lab manual. However, given the meagre peripherals and sensors available on the kit, we describe the design of Padma - a circuit board full of rich set of peripherals and sensors that connects to the Tiva Launchpad and exploits the rich on-chip features of the Tiva microcontroller family. Each and every resource of the microcontroller - Digital Input and output, Timers and counters, serial communication channels, analog to digital conversion, interrupt structure and power management features are involved in a set of more than 70 experiments to help teach a full semester course on these microcontrollers. However, beyond these exercises of physical interfacing, the lab manual describes an inexpensive BoB (Break Out Board) that allows the student to learn how to design and build standalone projects. A few illustrative projects are also described in the manual.
Introduction -- Chapter 1 ARM Cortex-M4 Core and Tiva C Series Peripherals -- Chapter Tiva C Series LaunchPad -- Chapter 2 PadmaBoard-Peripheral Motherboard of Tiva C Series LaunchPad -- Chapter 3 Tiva C Series Controller Breakout Board(BOB) -- Chapter 4 GNU ARM Toolchain -- Chapter 5 Anatomy of C Program -- Chapter 6 Application Programming Interface (API) -- Chapter 7 Digital Input/Output -- Chapter 8 Interrupts -- Chapter 9 Timers -- Chapter 10 Universal Asynchronous Receiver and Transmitter (UART) -- Chapter 11 Power Management and System Control -- Chapter 12  Analog to Digital Converter(ADC) -- Chapter 13 User Input/Output Devices -- Chapter 14 Tiva C Series Based Standalone Projects.
Keywords: Electronic circuits; Electronics; Microprogramming .; Signal processing; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation; Control Structures and Microprogramming; Signal, Speech and Image Processing